PERANAN LEMBAGA PENGEMBANGAN MASYARAKAT AMUNGME DAN KAMORO (LPMAK) DALAM PELAKSANAAN PROGRAM KEWIRAUSAHAAN DI KABUPATEN MIMIKA PAPUA - Munawaroh, Siti; Johnly Pio, Riane; Tumbel, Tinneke M. (Sam Ratulangi University, 2017)
This study aims to determine the role of the Amungme and Kamoro Community Development Institution (LPMAK) in the implementation of the Entrepreneurship Program and the welfare of indigenous peoples following the development of entrepreneurship carried out by LPMAK. This research was conducted at LPMAK office located in Mimika Papua Regency. The method used in this research is qualitative method. Sources of data used in this study are secondary data classified into two kinds, namely secondary external data and secondary internal data. The results of this study indicate that the role of LPMAK in community development ranging from training to financing productive economic enterprises carried out well in accordance with the target, the decline in the last few years due to PT Freeport Indonesia unstable which became the largest contributor of funds, resulting in a 40% cut of funds. Welfare can not be achieved thoroughly because society has not been able to change for the better so many solutions provided by LPMAK but few want to receive. With this community will be more active role to develop the entrepreneurial potential managed by LPMAK in order to achieve overall welfare. Â Keyword: Role, LPMAK, Entrepreneurship